Higher-Dose Sitagliptin and the Risk of Congestive Heart Failure in Older Adults with CKD - Muanda, Flory T. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Sitagliptin, a dipeptidyl peptidase-4 inhibitor, is commonly prescribed to patients with type 2 diabetes. As this drug is primarily eliminated by the kidney, a reduced dose is recommended for patients with CKD. Some evidence suggests that sitagliptin is associated with a higher risk of congestive heart failure, particularly at higher doses. We compare the 1-year risk of death or hospitalization with congestive heart failure in patients with CKD newly prescribed sitagliptin at >50 versus ≤50 mg/d. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This population-based cohort study included older adults (>66 years) with type 2 diabetes and an eGFR<45 ml/min per 1.73 m(2) (but not receiving dialysis) who were newly prescribed sitagliptin between 2010 and 2017 in Ontario, Canada. We used inverse probability of treatment weighting on the basis of propensity scores to balance baseline characteristics. The primary composite outcome was death or hospitalization with congestive heart failure. Secondary outcomes included hospitalization with pancreatitis or hypoglycemia, all-cause hospitalization, and glycemic control. Weighted hazard ratios were obtained using Cox proportional hazards regression, and 95% confidence intervals were obtained using bootstrap variance estimators. RESULTS: Of 9215 patients, 6518 started sitagliptin at >50 mg/d, and 2697 started sitagliptin at ≤50 mg/d. The 1-year risk of death or hospitalization with congestive heart failure did not differ significantly between groups (79 versus 126 events per 1000 person-years; weighted hazard ratio, 0.88; 95% confidence interval, 0.67 to 1.14); hospitalization with pancreatitis (weighted hazard ratio, 0.98; 95% confidence interval, 0.32 to 3.03) and hypoglycemia (weighted hazard ratio, 1.10; 95% confidence interval, 0.64 to 1.90) also did not differ significantly between groups. Patients starting sitagliptin at >50 mg/d had lower mean glycated hemoglobin concentrations (weighted between-group difference, −0.12%; 95% confidence interval, −0.19 to −0.06) and a lower risk of all-cause hospitalization (weighted hazard ratio, 0.81; 95% confidence interval, 0.66 to 0.98). CONCLUSIONS: The risk of death or congestive heart failure was not higher in older adults with CKD starting sitagliptin at >50 versus ≤50 mg/d. PODCAST: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2020_11_25_CJN08310520_final.mp3